Study of parameters to determinate the quality of seedlings of Coffea arábica L. cv. Mundo Novo, under shading - Miglioranza, Édison; Alliprandini, Luis Fernando; Fonseca, Ésio de Pádua; Koike, Roberto; Almeida, José Carlos Viera de (Semina: Ciências Agrárias, 1993)
<!–[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Parameters for seedlings selection of Coffea arábica L. cv. Mundo Novo, developed under different shading intensity, in Londrina-PR., were studied. Polypropylene sheets which retained 50, 55 and 60% of the global sun radiation were used. The best seedlings were obtained under 50% of shading. The plant height, stem diameter, dry weight of the aerial part, dry weight of the root system and leaf area showed direct correlation among themselves. All these parameters were negatively correlated with shading. The stem diameter was considered the best criteria to determine the standard quality of coffeee seedling, because it showed high correlation with the other parameters and it is easily measured by a non destructive method.